Juridical Analysis of the Impact of Online Application-Based Public Transportation of Motorcycle Taxis Regulation Policies (Case Study in Tangerang and surrounding areas) - hantoro, setyo; Santoso, Aris Prio; Guntara, Peter (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
It has been more than 14 years since motorized two-wheeled vehicles have been operating on the roads, through the "GOJEK" app, which can be downloaded from the Playstore. This has proven that this type of passenger and goods transportation can be an alternative solution for the community to become a primary source of income, thus improving family economies. It is now time for the government to provide a space for this new type of transportation to enter as a special transportation category with a "yellow" plate. The introduction of this new transportation system has created job opportunities for the wider community. From its establishment in 2010, starting with 10 people, it has grown to over 2 million people in 2024 who are now partners in the company. This system was also tested during the COVID-19 pandemic, which affected almost the entire world. Specifically in Indonesia, this type of transportation has proven to be very helpful. Operationally, this type of transport is relatively cheaper and highly affordable for its partners. One can imagine how many millions of people would lose their jobs if the government insists on not recognizing this type of transportation as a special transport fleet. It is referred to as special because: This type of fleet does not have a fixed base (such as a terminal) and usually operates from wherever, but currently, due to partner awareness, they gather at a specific point, becoming a gathering place for online motorcycle taxi partners. This type of fleet is similar to the commonly used vehicles on the road, with divided and separate routes. This type of fleet can go anywhere, which has become a point of contention for other vehicles that operate according to their designated routes. However, the presence of this type of fleet is already highly needed, and it is clearly proven that this type of transportation is more accessible to serve the community. Therefore, passengers do not need to walk far to use this transportation service. It is hoped that by officially recognizing this special transport service, it can improve safety and enhance the welfare of online motorcycle taxi partners across the country.